Calcineurin inhibitors and NFAT-regulated gene expression - Sommerer, Claudia; Meuer, Stefan; Zeier, Martin; Giese, Thomas (Clinica chimica acta, 2012)
Calcineurin inhibitors (CNIs) have a narrow therapeutic window; therefore, regular monitoring of the drug is necessary to balance sufficient efficacy with minimal toxicity. Until now, monitoring of immunosuppressive drugs is performed by pharmacokinetic assessments, mainly by trough concentrations (C0) of the drug. All these methods rely on pharmacokinetic data, which does not reflect the biological effects of CNI on the immune system. Several approaches have been undertaken to measure the biologic effects of CNI-based immunosuppression. Recently, a new quantitative analysis of gene expression has been employed to calculate the inhibition of the transcription of NFAT-regulated genes in peripheral blood. Methodological aspects and clinical data on the potential benefit of this specific CNI monitoring assay are discussed.